Puromycin A, B and C, cryptic nucleosides identified from Streptomyces alboniger NRRL B-1832 by PPtase-based activation - Xiaoli Yan; Benyin Zhang; Wenya Tian; Qi Dai; Xiaoqin Zheng; Ke Hu; Xinxin Liu; Zixin Deng; Xudong Qu (Synthetic and Systems Biotechnology, 2018)
Natural product discovery is pivot for drug development, however, this endeavor is often challenged by the wide inactivation or silence of natural products biosynthetic pathways. We recently developed a highly efficient approach to activate cryptic/silenced biosynthetic pathways through augmentation of the phosphopantetheinylation of carrier proteins. By applying this approach in the Streptomyces alboniger NRRL B-1832, we herein identified three cryptic nucleosides products, including one known puromycin A and two new derivatives (puromycin B and C). The biosynthesis of these products doesn't require the involvement of carrier protein, indicating the phosphopantetheinyl transferase (PPtase) indeed plays a fundamental regulatory role in metabolites biosynthesis. These results demonstrate that the PPtase-based approach have a much broader effective scope than the previously assumed carrier protein-involving pathways, which will benefit future natural products discovery and biosynthetic studies.